MODEL MANAJEMEN ZAKAT DI ARAB SAUDI: AKUNTABILITAS, TRANSPARANSI, DAN DAMPAK SOSIAL EKONOMI - Hasan Rahman Nasution; Maryam Batubara (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the zakat management model implemented in Saudi Arabia, examine the application of accountability and transparency principles in the process of collecting, managing, and distributing zakat, and assess the socioeconomic impact on community welfare and poverty alleviation. The method used is a literature review, which involves analyzing scientific publications, journals, and related reports to develop a solid conceptual framework. The main findings show that the zakat management model in Saudi Arabia, which is managed by the Zakat, Tax, and Customs Authority (ZATCA), implements a centralized and integrated system with the support of digital technology, layered audits, and the separation of fund collection and distribution. The implementation of accountability through internal-external audit mechanisms and transparency via blockchain and public dashboards has increased efficiency, public trust, and muzakki participation. The socioeconomic impact includes a reduction in poverty rates, the empowerment of mustahik through productive programs, and contributions to the achievement of the Sustainable Development Goals (SDGs) in the fields of education and health. The conclusion of this study emphasizes the effectiveness of the Saudi Arabian model as a reference for other countries in optimizing zakat as an instrument of social justice. Recommendations include empirical field studies and comparative analysis to deepen understanding of microeconomic impacts. This study contributes to the literature by filling the knowledge gap on the holistic evaluation of national zakat governance in the era of digitalization   Keywords: Zakat Saudi Arabia, Accountability, Transparency, Socioeconomic Impact   Abstrak: Penelitian ini bertujuan untuk menganalisis model manajemen zakat yang diterapkan di Arab Saudi, mengkaji penerapan prinsip akuntabilitas dan transparansi dalam proses pengumpulan, pengelolaan, serta pendistribusian zakat, serta menilai dampak sosial ekonomi terhadap kesejahteraan masyarakat dan pengentasan kemiskinan. Metode yang digunakan adalah literature review, yang melibatkan analisis terhadap publikasi ilmiah, jurnal, dan laporan terkait untuk menyusun kerangka konseptual yang kokoh. Temuan utama menunjukkan bahwa model manajemen zakat di Arab Saudi, yang dikelola oleh Zakat, Tax, dan Customs Authority (ZATCA), menerapkan sistem terpusat dan terintegrasi dengan dukungan teknologi digital, audit berlapis, serta pemisahan penghimpunan dan pendistribusian dana. Penerapan akuntabilitas melalui mekanisme audit internal-eksternal dan transparansi via blockchain serta dashboard publik telah meningkatkan efisiensi, kepercayaan masyarakat, dan partisipasi muzakki. Dampak sosial ekonomi mencakup penurunan angka kemiskinan, pemberdayaan mustahik melalui program produktif, serta kontribusi terhadap pencapaian Sustainable Development Goals (SDGs) di bidang pendidikan dan kesehatan. Kesimpulan penelitian ini menekankan efektivitas model Arab Saudi sebagai referensi bagi negara lain dalam mengoptimalkan zakat sebagai instrumen keadilan sosial. Rekomendasi meliputi studi empiris lapangan dan analisis komparatif untuk memperdalam pemahaman dampak mikro-ekonomi. Penelitian ini berkontribusi terhadap literatur dengan mengisi gap pengetahuan tentang evaluasi holistik tata kelola zakat nasional dalam era digitalisasi.   Kata Kunci: Zakat, Arab Saudi, Akuntabilitas, Transparansi, Dampak Sosial Ekonomi